Portrait of John Howard - Milligan, Terry, 1941- (1999)
Photograph taken at the opening of the National Portrait Gallery, 4/3/99.
Condition: good.
Title from accession record.
Also available online
Keywords: Howard, John, -- 1939- -- Portraits; Politicians -- Australia -- Portraits; Prime ministers -- Australia -- Portraits; Federal politicians